2008
DOI: 10.1016/j.bbi.2007.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmune mechanisms of opioid-mediated conditioned immunomodulation

Abstract: Morphine administration elicits pronounced effects on the immune system, including decreases in natural killer (NK) cell activity and lymphocyte mitogenic responsiveness. These immune alterations can become conditioned to environmental stimuli that predict morphine as a result of Pavlovian conditioning processes. Prior work in our laboratory has shown that acute morphine exposure produces dopamine-dependent reductions of NK cell activity that are mediated peripherally by neuropeptide Y Y1 receptors. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…We determined that IL-10 protein was significantly increased in serum following morphine treatment in both groups, though significantly less so in handled rats, consistent with the literature indicating that morphine is immunosuppressive within the periphery (Sacerdote, 2008; Budd, 2006). We suspect that the differential glial response within the NAcc may be driving the differential peripheral immunosuppressive response between these groups, and consistent with this idea others have reported that the NAcc is necessary for the peripheral immunosuppression induced by morphine (Saurer et al, 2008; Saurer et al, 2009). Nonetheless, the contribution of peripheral immune cells to morphine reward and relapse and their modulation by early-life experience cannot be completely ruled out.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We determined that IL-10 protein was significantly increased in serum following morphine treatment in both groups, though significantly less so in handled rats, consistent with the literature indicating that morphine is immunosuppressive within the periphery (Sacerdote, 2008; Budd, 2006). We suspect that the differential glial response within the NAcc may be driving the differential peripheral immunosuppressive response between these groups, and consistent with this idea others have reported that the NAcc is necessary for the peripheral immunosuppression induced by morphine (Saurer et al, 2008; Saurer et al, 2009). Nonetheless, the contribution of peripheral immune cells to morphine reward and relapse and their modulation by early-life experience cannot be completely ruled out.…”
Section: Discussionsupporting
confidence: 81%
“…Taken together, these data indicate that morphine is immunosuppressive within the periphery, but that neonatal handling does not program baseline IL-10 expression within the peripheral immune system as it does within the brain. Rather, we hypothesize that the difference in peripheral immunosuppression following morphine administration between handled and non-handled control rats is driven by the differential glial response within the NAcc as it has been reported that the NAcc is necessary for the peripheral immunosuppression induced by morphine (Saurer et al, 2008; Saurer et al, 2009). …”
Section: Resultsmentioning
confidence: 90%
“…Opioid peptides are well known effectors of in vivo and in vitro immune responses. Furthermore, it has been shown that the opioids have broad immunomodulatory activity, both on cellular and humoral immune responses and are able to modulate inflammatory cytokine production [9][10][11]. This immunomodulatory activity is mediated by either the µ, δ or κ opioid receptors that are expressed on immune cells.…”
Section: Introductionmentioning
confidence: 98%
“…In support of this, inactivation of the BLA and blockade of dopamine D 1 -like receptors within the BLA prevent the suppressive effect of the heroin-associated context on iNOS induction and on TNF-α and IL-1β expression in spleen and liver tissue (Szczytkowski and Lysle, 2008, 2010). Dopamine D 1 -like receptor antagonism in the NAc shell blocks the expression of morphine-induced conditioned immune alterations (Saurer et al, 2008b). In a recent functional disconnection study from our laboratory (Szczytkowski et al, 2011), we provided evidence that the NAc plays a critical role in heron-conditioned immunomodulation as an element of a larger VTA-BLA-NAc circuit.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from our laboratory demonstrated that dopamine receptor activity was necessary for the expression of opioid-conditioned immune alterations, as administration of a D 1 -like receptor antagonist prior to re-exposure to a morphine-conditioned stimulus prevented the suppression of natural killer cell activity (Saurer et al, 2008a). Similar immunomodulatory effects have also been demonstrated with heroin (Fecho and Lysle, 2000; Lysle and Ijames, 2002; Saurer et al, 2008a). …”
Section: Introductionmentioning
confidence: 99%